Oncorine, the World First Oncolytic Virus Medicine and its Update in China - Liang, Min (Current Cancer Drug Targets, 2018)
The oncolytic viruses now hold a promise of new therapeutic strategy for cancer. Its concept has inspired a wave of commercial research and development activities for the products of this category in China since 1998. The first commercialized oncolytic virus product in the world, Oncorine (H101), developed by Shanghai Sunway Biotech Co., Ltd since 1999, was approved by Chinese SFDA in November, 2005 for nasopharyngeal carcinoma in combination with chemotherapy after the phase III clinical trial, and finally acquired GMP certificate in August, 2006. This review introduces how Oncorine was successfully developed in China, and how the Chinese market responded after it was launched into the market in 2006.
Keywords: chemotherapy